2016
DOI: 10.1007/s40474-016-0101-y
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Spectrum Disorders (FASD): an Approach to Effective Prevention

Abstract: Purpose of ReviewThe objective of the current contribution is to propose an evidence-based, six-step approach to develop effective programs for prevention of fetal alcohol spectrum disorders.Recent FindingsDespite widespread campaigns aimed to reduce prenatal alcohol exposure, the number of affected children continues to be high. Current strategies to reduce prenatal alcohol exposure may be ineffective or counterproductive. However, proven principles of health promotion could be applied to reduce drinking in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…In light of this, we may need to reframe discussions around harm prevention or whether there is a potentially ‘safe’ threshold, to messages about the importance of alcohol abstinence in optimising health and cognitive outcomes for the unborn child. At the population level, FASD-specific mass media campaigns, based on proven behaviour change principles and with messages which combine threat (addressing perceived susceptibility and severity) and self-efficacy (promoting confidence in ability to abstain) have been shown to be effective in the past [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, we may need to reframe discussions around harm prevention or whether there is a potentially ‘safe’ threshold, to messages about the importance of alcohol abstinence in optimising health and cognitive outcomes for the unborn child. At the population level, FASD-specific mass media campaigns, based on proven behaviour change principles and with messages which combine threat (addressing perceived susceptibility and severity) and self-efficacy (promoting confidence in ability to abstain) have been shown to be effective in the past [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, further study of approaches combining strategies at both the individual and community levels is important. Future work could incorporate some, or all, of these elements in addressing the behavioural and environmental factors that lead to PAE, whilst ensuring that each component is founded on sound theoretical models of health behaviour [ 66 , 67 ]. Lessons can be learnt from smoking intervention research where the use of such models has provided direction for successful program design and consequent behaviour change [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is concerning that none of the studies identified in this review adequately evaluated prevention efforts. FASD prevention in Indigenous communities could benefit from systematic approaches to program design, implementation, and evaluation [ 67 ]. High quality intervention trials with rigorous evaluation methods need to be conducted before any conclusions can be drawn about how best to prevent FASD.…”
Section: Discussionmentioning
confidence: 99%
“…Active case ascertainment (ACA) in schools has successfully determined the prevalence and characteristics of FASD in communities in South Africa, Italy, and Croatia (May et al, 2000, 2006, 2007, 2011, 2013, 2016a, 2016b, 2017; Petkovic and Barisic, 2010, 2013; Urban et al, 2008, 2015; Viljoen et al, 2002, 2005). ACA is also a robust method for linking maternal characteristics to child outcomes (May and Gossage, 2001; Roozen et al, 2016a, 2018; Stratton et al, 1996). In ACA studies, physical examinations and neurobehavioral testing are provided to children to determine their characteristic traits (Adnams et al, 2001; Aragon et al, 2008; Kalberg et al, 2013; Kodituwakku et al, 2006), and mothers are interviewed about alcohol use and other health‐related behavior during the index pregnancy (Ceccanti et al, 2014; May et al, 2005, 2008, 2010, 2013; Viljoen et al, 2002).…”
Section: Active Case Ascertainmentmentioning
confidence: 99%